Phylogenetic and phenotypic relationships of the Triatoma sordida subcomplex (Hemiptera: Reduviidae: Triatominae) - BELINTANI, TIAGO; OLIVEIRA, JADER [UNESP]; PINOTTI, HELOISA [UNESP]; SILVA, LUCAS ABRANTES [UNESP]; ALEVI, KAIO CESAR CHABOLI [UNESP]; GALVÃO, CLEBER; ROSA, JOÃO ARISTEU DA [UNESP] (Elsevier, 2020)
Chagas disease, whose etiological agent is the protozoan Trypanosoma cruzi, affects millions of people worldwide and it is mainly transmitted by infected triatomine feces. Triatoma is the most diverse genus and one of the most important from an epidemiological point of view. Species of this genus are grouped into eight complexes and nine subcomplexes. Triatoma sordida subcomplex consists of T. garciabesi, T. guasayana, T. patagonica, and, T. sordida. Given the recent discussions on their phylogenetic status, this study aims to evaluate morphometric and genetics characters that group and distinguish T. garciabesi, T. guasayana, T. patagonica, and T. sordida, as well as to infer the phylogenetic relationships within the group and evaluate the proximity with T. rubrovaria subcomplex. The results corroborate the phylogenetic relationship of T. guasayana and T. patagonica with the T. rubrovaria subcomplex. Molecular data confirm the proximity of T. jurbergi, T. matogrossensis, T. vandae as T. garciabesi, and T. sordida. Together, genetic variability was shown between T. sordida populations.
Keywords: Chagas disease vectors; Phylogenetic; T. sordida subcomplex; Triatominae